The Effect of E-WOM on Social Media Marketing on Purchase Intention (Case Study: Gallery Vinna) - Rizka Utami, Fany; Ariyanti, Maya; Millanyani, Heppy (International Journal of Science, Technology & Management, 2024)
This study aims to determine the effect of social media marketing through online word of mouth on purchase intention on the Tiktok Gallery Vinna platform as the object of research. The research method used is quantitative method, using an online survey by collecting 155 respondents. The data collected was analyzed with Smart PLS software to test the research hypothesis. The results showed that respondents' responses to Tiktok Gallery Vinna's social media received a good response, and respondents felt that the uploaded content could provide interesting and easy-to-understand information. Then, e-WOM has a significant effect on buying interest, and social media has the most influence on buying interest. The results also show that providing the latest information by utilizing social media can expand the network to attract buying interest in consumers. Therefore, this study examines the Tiktok platform which expands knowledge about the factors that influence attitudes and purchase intentions towards consumers through e-WOM, as well as the use of social media that have an impact on consumer purchase intentions. This research provides insight for SMEs who want to improve marketing strategies using social media.